Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's solve this problem step-by-step.
We are given that [tex]\(\sin(u) = -\frac{7}{25}\)[/tex] and [tex]\(\cos(v) = -\frac{4}{5}\)[/tex], and both [tex]\(u\)[/tex] and [tex]\(v\)[/tex] are in quadrant III. In quadrant III, both sine and cosine functions are negative.
### Step 1: Finding [tex]\(\cos(u)\)[/tex]
To find [tex]\(\cos(u)\)[/tex], we use the Pythagorean identity:
[tex]\[ \sin^2(u) + \cos^2(u) = 1 \][/tex]
Given [tex]\(\sin(u) = -\frac{7}{25}\)[/tex]:
[tex]\[ \left( -\frac{7}{25} \right)^2 + \cos^2(u) = 1 \][/tex]
[tex]\[ \frac{49}{625} + \cos^2(u) = 1 \][/tex]
[tex]\[ \cos^2(u) = 1 - \frac{49}{625} \][/tex]
[tex]\[ \cos^2(u) = \frac{625}{625} - \frac{49}{625} \][/tex]
[tex]\[ \cos^2(u) = \frac{576}{625} \][/tex]
Since [tex]\(u\)[/tex] is in the third quadrant, [tex]\(\cos(u)\)[/tex] is negative:
[tex]\[ \cos(u) = -\sqrt{\frac{576}{625}} = -\frac{24}{25} \][/tex]
### Step 2: Finding [tex]\(\sin(v)\)[/tex]
We now use the Pythagorean identity to find [tex]\(\sin(v)\)[/tex]:
[tex]\[ \sin^2(v) + \cos^2(v) = 1 \][/tex]
Given [tex]\(\cos(v) = -\frac{4}{5}\)[/tex]:
[tex]\[ \sin^2(v) + \left( -\frac{4}{5} \right)^2 = 1 \][/tex]
[tex]\[ \sin^2(v) + \frac{16}{25} = 1 \][/tex]
[tex]\[ \sin^2(v) = 1 - \frac{16}{25} \][/tex]
[tex]\[ \sin^2(v) = \frac{25}{25} - \frac{16}{25} \][/tex]
[tex]\[ \sin^2(v) = \frac{9}{25} \][/tex]
Since [tex]\(v\)[/tex] is in the third quadrant, [tex]\(\sin(v)\)[/tex] is negative:
[tex]\[ \sin(v) = -\sqrt{\frac{9}{25}} = -\frac{3}{5} \][/tex]
### Step 3: Finding [tex]\(\cos(u - v)\)[/tex]
Use the cosine angle subtraction formula:
[tex]\[ \cos(u - v) = \cos(u) \cos(v) + \sin(u) \sin(v) \][/tex]
Substitute the known values:
[tex]\[ \cos(u - v) = \left( -\frac{24}{25} \right) \left( -\frac{4}{5} \right) + \left( -\frac{7}{25} \right) \left( -\frac{3}{5} \right) \][/tex]
Perform the multiplications:
[tex]\[ \cos(u - v) = \frac{96}{125} + \frac{21}{125} \][/tex]
Add the results:
[tex]\[ \cos(u - v) = \frac{96 + 21}{125} = \frac{117}{125} \][/tex]
Hence, the exact value of [tex]\(\cos(u - v)\)[/tex] is:
[tex]\[ \boxed{\frac{117}{125}} \][/tex]
We are given that [tex]\(\sin(u) = -\frac{7}{25}\)[/tex] and [tex]\(\cos(v) = -\frac{4}{5}\)[/tex], and both [tex]\(u\)[/tex] and [tex]\(v\)[/tex] are in quadrant III. In quadrant III, both sine and cosine functions are negative.
### Step 1: Finding [tex]\(\cos(u)\)[/tex]
To find [tex]\(\cos(u)\)[/tex], we use the Pythagorean identity:
[tex]\[ \sin^2(u) + \cos^2(u) = 1 \][/tex]
Given [tex]\(\sin(u) = -\frac{7}{25}\)[/tex]:
[tex]\[ \left( -\frac{7}{25} \right)^2 + \cos^2(u) = 1 \][/tex]
[tex]\[ \frac{49}{625} + \cos^2(u) = 1 \][/tex]
[tex]\[ \cos^2(u) = 1 - \frac{49}{625} \][/tex]
[tex]\[ \cos^2(u) = \frac{625}{625} - \frac{49}{625} \][/tex]
[tex]\[ \cos^2(u) = \frac{576}{625} \][/tex]
Since [tex]\(u\)[/tex] is in the third quadrant, [tex]\(\cos(u)\)[/tex] is negative:
[tex]\[ \cos(u) = -\sqrt{\frac{576}{625}} = -\frac{24}{25} \][/tex]
### Step 2: Finding [tex]\(\sin(v)\)[/tex]
We now use the Pythagorean identity to find [tex]\(\sin(v)\)[/tex]:
[tex]\[ \sin^2(v) + \cos^2(v) = 1 \][/tex]
Given [tex]\(\cos(v) = -\frac{4}{5}\)[/tex]:
[tex]\[ \sin^2(v) + \left( -\frac{4}{5} \right)^2 = 1 \][/tex]
[tex]\[ \sin^2(v) + \frac{16}{25} = 1 \][/tex]
[tex]\[ \sin^2(v) = 1 - \frac{16}{25} \][/tex]
[tex]\[ \sin^2(v) = \frac{25}{25} - \frac{16}{25} \][/tex]
[tex]\[ \sin^2(v) = \frac{9}{25} \][/tex]
Since [tex]\(v\)[/tex] is in the third quadrant, [tex]\(\sin(v)\)[/tex] is negative:
[tex]\[ \sin(v) = -\sqrt{\frac{9}{25}} = -\frac{3}{5} \][/tex]
### Step 3: Finding [tex]\(\cos(u - v)\)[/tex]
Use the cosine angle subtraction formula:
[tex]\[ \cos(u - v) = \cos(u) \cos(v) + \sin(u) \sin(v) \][/tex]
Substitute the known values:
[tex]\[ \cos(u - v) = \left( -\frac{24}{25} \right) \left( -\frac{4}{5} \right) + \left( -\frac{7}{25} \right) \left( -\frac{3}{5} \right) \][/tex]
Perform the multiplications:
[tex]\[ \cos(u - v) = \frac{96}{125} + \frac{21}{125} \][/tex]
Add the results:
[tex]\[ \cos(u - v) = \frac{96 + 21}{125} = \frac{117}{125} \][/tex]
Hence, the exact value of [tex]\(\cos(u - v)\)[/tex] is:
[tex]\[ \boxed{\frac{117}{125}} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.